2018
DOI: 10.1101/257865
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A distributed brain network predicts general intelligence from resting-state human neuroimaging data

Abstract: Individual people differ in their ability to reason, solve problems, think abstractly, plan and learn. A reliable measure of this general ability, also known as intelligence, can be derived from scores across a diverse set of cognitive tasks. There is great interest in understanding the neural underpinnings of individual differences in intelligence, since it is the single best predictor of long-term life success, and since individual differences in a similar broad ability are found across animal species. The m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
149
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(172 citation statements)
references
References 120 publications
(203 reference statements)
17
149
6
Order By: Relevance
“…Using simulations and empirical data, we have shown that incorporating effect sizes across all vertices, using the PVS method, explained more variance in behavior than thresholding vertices based on significance level. Consistent with association patterns reported in other task-based fMRI studies (Chang et al, 2015;Gonzalez-Castillo et al, 2012) and for other brain phenotypes (Dubois et al, 2018;Palmer et al, in prep;Smith et al, 2015), the explanatory effect of these functional brain phenotypes on the behaviors tested was widespread and distributed across the cortex. Our results provide an empirical evidence that it is important to account for the whole brain pattern of association when studying brain-behavior relationships.…”
Section: Discussionsupporting
confidence: 87%
“…Using simulations and empirical data, we have shown that incorporating effect sizes across all vertices, using the PVS method, explained more variance in behavior than thresholding vertices based on significance level. Consistent with association patterns reported in other task-based fMRI studies (Chang et al, 2015;Gonzalez-Castillo et al, 2012) and for other brain phenotypes (Dubois et al, 2018;Palmer et al, in prep;Smith et al, 2015), the explanatory effect of these functional brain phenotypes on the behaviors tested was widespread and distributed across the cortex. Our results provide an empirical evidence that it is important to account for the whole brain pattern of association when studying brain-behavior relationships.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, future work should examine the generalizability of these neural network models to depression in adolescent males. In addition, recent evidence has suggested that task‐based connectivity models outperform resting‐state connectivity models in predicting fluid intelligence (Greene, Gao, Scheinost, & Constable, ), and resting‐state connectivity models were associated with higher‐order latent‐factors stronger than lower‐order cognitive task scores (Dubois, Galdi, Paul, & Adolphs, ). This indicates that engaging networks in targeted domains can improve the predictability of individual differences.…”
Section: Discussionmentioning
confidence: 99%
“…A similar strategy has been successfully employed to create a phenotypic measure of intelligence across individual measures of crystallized ability, processing speed, visuospatial ability and memory (Dubois et al, 2018). To maintain separate train and test groups, for each iteration, each PCA was limited to training datasets and these PCA coefficients were subsequently applied to the test dataset (see Figure 1.C).…”
Section: Principal Components Analysismentioning
confidence: 99%
“…We performed a series of predictive and explanatory analyses of the brain's functional connectome . Functional connectomes have been shown to be unique to an individual (Finn et al, 2015), stable over a lifespan (Horien, Shen, Scheinost, & Constable, 2019), and predictive of clinical and cognitive traits in novel subjects (Dubois, Galdi, Paul, & Adolphs, 2018;Rosenberg et al, 2016). Though connectomes are typically based on resting-state fMRI, task-based fMRI has been shown to improve the prediction of individual cognitive traits and more clearly delineate brain-behavior relationships (Greene, Gao, Scheinost, & Constable, 2018).…”
Section: Introductionmentioning
confidence: 99%